1974
DOI: 10.1159/000178640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dexamethasone on Bone Marrow Erythropoiesis

Abstract: A stimulatory effect on bone marrow erythroid cells was observed in normal rats treated with dexamethasone. The erythropoietic effects of dexamethasone were completely abolished in rats with bilateral nephrectomy. In addition, simultaneous administration of corticosteroid with antibodies against erythropoietin in normal rats also resulted in a complete inhibition of the stimulatory action of dexamethasone on the bone marrow erythroid compartment. These results suggest that dexamethasone stimulates erythropoies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
1

Year Published

1976
1976
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 5 publications
2
10
1
Order By: Relevance
“…74 showed an antagonistic effect on the T3 action. This blocking effect of T 4 on T 3 action is unusual, since the biological potence of T4 is similar or lower than T3, but both hormones act in the same direction [19][20][21][27][28][29]. This finding represents, to the best of our knowledge, the first observation of an hormonal blocking action of the T4 on T 3.…”
Section: Blocking Effect Of T4 On the Ts Actionsupporting
confidence: 50%
See 1 more Smart Citation
“…74 showed an antagonistic effect on the T3 action. This blocking effect of T 4 on T 3 action is unusual, since the biological potence of T4 is similar or lower than T3, but both hormones act in the same direction [19][20][21][27][28][29]. This finding represents, to the best of our knowledge, the first observation of an hormonal blocking action of the T4 on T 3.…”
Section: Blocking Effect Of T4 On the Ts Actionsupporting
confidence: 50%
“…However, several workers suggested that T4 could have a true biological activity per se [27][28][29]. Some membrane systems were affected by thyroid hormones [30][31][32][33] ; in our case, T3 decreased membrane fluidity.…”
Section: Blocking Effect Of T4 On the Ts Actionmentioning
confidence: 43%
“…Addison's disease in man is associated with normocytic, normochromic anemia (18), and a congenital erythroid hy- poplasia of children (Diamond-Blackfan syndrome) is frequently responsive to low doses of glucocorticoids (19). In animals, glucocorticosteroids and ACTH have been reported to stimulate erythropoiesis (20)(21)(22) but inhibition has also been observed (23,24) On the basis. of observations in nephrectomized rats, Malgor and coworkers (22) concluded that dexamethasone stimulated erythropoiesis by an effect on erythropoietin production.…”
Section: Introductionmentioning
confidence: 99%
“…In animals, glucocorticosteroids and ACTH have been reported to stimulate erythropoiesis (20)(21)(22) but inhibition has also been observed (23,24) On the basis. of observations in nephrectomized rats, Malgor and coworkers (22) concluded that dexamethasone stimulated erythropoiesis by an effect on erythropoietin production. Glucocorticoids are also reported to stimulate erythropoiesis in amphibians (25).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the TR␣ isoform is expressed preferentially in differentiating erythroid cells (14) and that the v-erbA oncogene involved in avian erythroleukemia represents a mutated form of TR␣ (15,16). Studies with whole animals have indicated that T 3 stimulates erythropoiesis (17), whereas in vitro assays have shown that T 3 inhibits colony formation by erythroid progenitors (18,19). The elegant studies of Beug and colleagues (19 -24) have demonstrated that the balance between proliferation and differentiation can be altered by the introduction of exogenous TR␣ (cerbA) or v-erbA into immature avian red blood cells.…”
mentioning
confidence: 99%